The Effectiveness of celery leaf decoction and progressive muscle relaxation in lowering blood pressure - Haryanti, Indah Dwi; Meri, Dilgu; Ramadiya, Arya; Redo, Ahmad (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Hypertension is one of the leading non-communicable diseases causing global mortality, with an increasing prevalence, including in Indonesia. Both pharmacological and non-pharmacological approaches are employed in managing hypertension. One non-pharmacological therapy is the administration of celery leaf decoction (Apium graveolens L.), which contains active compounds such as flavonoids and phthalides with potential blood pressure-lowering effects. Additionally, Progressive Muscle Relaxation (PMR) techniques are effective in reducing blood pressure through physical and mental relaxation. Method: The study employed a quasi-experimental design with a pretest-posttest without control group approach. The subjects were hypertensive patients at Adhyaksa Clinic, selected through purposive sampling. Data were analyzed using the Wilcoxon signed-rank test. Results: The abstract contains background (a brief description of the problem and research objectives) methods used, the results of the research, and conclusions (indicate the main conclusions). Conclusion: The majority of respondents were male (71.4%), aged 41–45 years (42.9%), held a bachelor's degree (85.7%), and worked as prosecutors (66.7%). The average systolic and diastolic blood pressures before the intervention were 149.52 mmHg and 89.52 mmHg, respectively, which decreased to 126.19 mmHg and 74.29 mmHg after the intervention. The analysis showed that celery leaf decoction and PMR movements were effective in reducing blood pressure, with a p-value of 0.000 (< 0.05).